Leprosy incidence, characterization of cases and correlation with household and cases variables of the Brazilian states in 2010 - Shamyr Sulyvan de Castro; Juliana Pereira Pontes Santos; Graziela Basílio Abreu; Vanessa Rossato Oliveira; Luciane Fernanda Rodrigues Martinho Fernandes (Sociedade Brasileira de Dermatologia, 2016)
Abstract BACKGROUND: Leprosy is millenary disease and still persists in several countries. OBJECTIVES: To estimate the incidence of leprosy in the Brazilian states and for the country in the year 2010; to describe the cases reported according to the studied variables; to verify the correlation between the overall incidence and the studied variables. METHODS: Ecological descriptive study, with population data from the 27 states, 2010. Information about reported cases were collected: gender, race, percentage of patients younger than 15 years old and living conditions. The analysis was performed using percentages, means, incidence rates and the Spearman correlation test. RESULTS: The states of Mato Grosso and Tocantins recorded the highest incidence rates; Rio Grande do Sul and Santa Catarina, the lowest; there was a higher incidence of leprosy among men; the incidence of leprosy increases proportionally with the nonwhites among the inhabitants; patients younger than 15 years; the average number of residents per household; and a decrease in coverage of water supply and presence of bathrooms. CONCLUSION: The incidence of leprosy is related to factors as gender, race and house conditions (p<0,05 for all).